Analysis of Transformational Leadership Dimensional in Improving Knowledge Management of Village Official in Sungai Penuh City - Ferry Siswadhi; Gampo Haryono; Kasman Karimi (Yayasan Ilomata, 2023)
A leader is said to be transformational when he can inspire his subordinates to accept the vision of the organization as his own while trying to improve the values of his organization. In the organization, the role of the leader is very big for the achievement of the goals of the organization. This study aims to analyze the Dimensions of Transformational Leadership in Improving Knowledge Management of Village Official in Sungai Penuh City. This research was conducted in Sungai Penuh City with village officials as research subjects. Details of 69 villages in Sungai Penuh City with case studies located in 3 sub-districts, namely Kumun Debai District, Pondok Tinggi District, and Sungai Bungkal District. So from 3 sub-districts with 21 villages, the number of respondents in this study was 124 village officials. Sources of data were obtained from interviews (interviews) and a list of questions (questionnaires). This research uses Structural Equation Models (SEM) data analysis and uses AMOS as an analytical tool. The results showed that the large influence of the dimensions of Transformational leadership which consisted of four consisting of Idealized influence, Individualized consideration, Inspirational motivation, and Intellectual stimulation had an effect of 44.7% on Transformational leadership in Village Official in Sungai Penuh City. Transformational leadership has an effect of 13.3% on the knowledge management of village officials in Sungai Penuh City.